Using a Social Justice Lens to Connect the Past with the Present in a Personalized Learning Environment - Kyle Chadburn; Andrea Gratton (Middle Grades Review, 2021)
This practitioner perspective describes how middle grades units are developed and revised in response to student needs to engage students in social justice work while maintaining a safe and respectful classroom culture. In order for students to understand the world around them, they need to develop context by studying the past. There is no better way to enable students to do this in a personalized learning environment than to explore both the past and present through the lens of social justice. Broad, thematic units, such as “Revolution,” “Race in America,” or “Societal Monsters” allow teachers to ensure that students are able to analyze and reflect on the injustices of the past, as well as understand how those injustices have changed and shifted to become the ones we see and experience in our modern world. At the same time, personalized learning allows students the freedom to choose topics within these broad themes and learning pathways that suit their interests, skills, and needs as individuals.
Keywords: personalized learning; social justice; middle school; young adolescents